Combining ability of wheat genotypes estimated by multivariate analysis - Benin, Giovani; Silva, Giovani Olegário da; Pagliosa, Eduardo Stefani; Lemes, Cristiano; Signorini, Anderson; Beche, Eduardo; Capelin, Marcio Andrei (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to estimate the combining ability of wheat lines using multivariate analysis, in order to identify crossing combinations with superior performance. Eight wheat parental lines were crossed in a complete diallel design without reciprocals. Crosses and advanced generations were obtained in the year 2007 in a full-line sowing system, and the hybrids were evaluated in 2008, in a randomized block design with three replicates. The data were treated using and multivariate , principal component analysis, and partial and multivariate diallel analyses. The cultivar BRS Guamirim was the parental genotype with the best performance for general combining ability for group 1 traits (grain yield, thousand grains weight, spike weight and number of grains per spike), whereas the cultivar Fundacep Raízes was the best for group 2 traits (days from emergence to bloom, days from bloom to maturation, and plant height). 'BRS Guamirim' x 'Fundacep Cristalino' (for group 1 traits) and 'Abalone' x 'Fundacep Cristalino' and 'Abalone' x 'Fundacep Raízes' (for group 2 traits) were the best crossings for specific combining ability.